2021
DOI: 10.3389/fbioe.2021.730925
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photothermal Effects of Intracellular Aggregating Nanodrugs Targeting Nasopharyngeal Carcinoma

Abstract: Chemotherapy for the treatment of nasopharyngeal carcinoma (NPC) is usually associated with many side effects; therefore, its treatment options have not yet been completely resolved. Improving distribution to the targeted tumor region and enhancing the cellular uptake of drugs can efficiently alleviate the above adverse medical effects. Near-infrared (NIR) laser light-mediated photothermal therapy (PTT) and photodynamic therapy (PDT) are promising strategies for cancer treatment. In the present study, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Zhong et al successfully synthesized an efficient multifunctional nanocluster (NPs FA-PEG/CBT@ SPION-ICG) and enhanced the targeting and aggregation efficiency for PTT and PDT. 85 As displayed in Figure 6 , the outcomes indicated that FA-PEG/CBT@SPION-ICG combined with PTT/PDT had a good therapeutic effect on nude mice bearing HNE-1 tumors compared with the control-treated groups. Furthermore, FA-PEG/CBT@SPION-ICG is biologically safe and is expected to be a complementary treatment model for HNE-1 NPC.…”
Section: Optical Treatment Strategies For Npcmentioning
confidence: 91%
See 1 more Smart Citation
“…Zhong et al successfully synthesized an efficient multifunctional nanocluster (NPs FA-PEG/CBT@ SPION-ICG) and enhanced the targeting and aggregation efficiency for PTT and PDT. 85 As displayed in Figure 6 , the outcomes indicated that FA-PEG/CBT@SPION-ICG combined with PTT/PDT had a good therapeutic effect on nude mice bearing HNE-1 tumors compared with the control-treated groups. Furthermore, FA-PEG/CBT@SPION-ICG is biologically safe and is expected to be a complementary treatment model for HNE-1 NPC.…”
Section: Optical Treatment Strategies For Npcmentioning
confidence: 91%
“…Creative Commons license and disclaimer available from: http://creativecommons.org/licenses/by/4.0/legalcode . 85 …”
Section: Optical Treatment Strategies For Npcmentioning
confidence: 99%
“…PDT treatment with NIR light on a single tumor in mice bearing two tumors on opposite flanks significantly inhibited tumor growth in the treated tumors compared to the internal control tumor or versus animals treated with NIR light alone, the PS alone, or untreated animals. Of note, the clinically approved indocyanine green (ICG) is a fluorescent dye that was investigated extensively in the preclinical setting due to its diagnostic and therapeutic properties [ 244 , 245 , 246 , 247 , 248 , 249 ], but its instability in the body has hampered its use in the clinic. To this end, an encapsulated form of ICG was investigated in patients, showing an improved clinical response against basal cell carcinoma [ 250 ].…”
Section: Light Propagation Through Tissuesmentioning
confidence: 99%
“…The PDT technique lessens the need for extensive surgery and speeds up recovery; furthermore, it is capable of being performed without accumulating adverse effects and may be used in conjunction with conventional therapies [8]. PDT is also effective against several drug-resistant malignancies, such as nasopharyngeal carcinoma [210], breast cancer [211], uterine sarcoma [212], and gastric cancer [213] as shown in (figure 7). In the next section, the mode of action of various NP-based photodynamic therapies for MDR malignancies will be discussed.…”
Section: Therapeutic Approaches Of Np-mediated Pdt In Multi-drug Resi...mentioning
confidence: 99%